Cyclic degradation and pore pressure dynamics of EICP treated hydrocarbon contaminated sands - Singh A.; Paramkusam B.R.; Maiti P.R. (My University, 2025)
Enzyme-induced carbonate precipitation (EICP) is an innovative bio-inspired approach that has emerged in recent years, offering a more environmentally sustainable option for soil improvement. The present article aims at extensively examining the effect of EICP treatment on the cyclic response of silty sands containing petroleum hydrocarbon compounds. Strain-controlled cyclic triaxial tests have been carried out on hydrocarbon contaminated sand with and without EICP treatment. Several independent variables such as hydrocarbon content (2, 4, 6, 8, and 10%), shear strain amplitudes (0.5% and 1%), and curing period (7 days and 14 days) were considered in the study. Prior to this, a baseline analysis was conducted to determine the effect of EICP treatment solution composition on the efficiency of carbonate precipitation. The effectiveness of the treatment was systematically investigated based on cyclic pore pressure response and degradation of cyclic shear modulus. The results revealed that petroleum contamination moderately increases the cyclic resistance up to a transition point beyond which it falls off sharply. The coupled effect of increasing oil content and curing time of EICP treatment has also been assessed. The variation of cyclic strength with crude oil content results in a single-peaked profile for both untreated and treated specimens. EICP treatment increases the cyclic resistance of oil-contaminated sand up to 1.5 times by suppressing the excess pore pressure build-up. A signification recovery in the degradation parameter, as high as 80%, was also observed. However, with increasing oil content and shear strain levels, the efficacy of EICP treatment exhibited a remarkable decline. The microstructural mechanism believed to be responsible for such a behavior has also been discussed. © 2020 Elsevier Ltd